KENDALA PERAN PEREMPUAN DALAM PENGURANGAN RESIKO BENCANA GEMPA BUMI DAN TSUNAMI DI KELURAHAN AIR TAWAR BARAT - Khairunnisa Khairunnisa; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aims to find out what are the constraints on the role of women in reducing the risk of the earthquake and tsunami disaster in Air Tawar Barat Village. women were the most vulnerable group when the earthquake and tsunami occurred. In the research conducted using a qualitative descriptive method. The technique of determining research informants by means of purposive sampling. Data collection techniques by means of observation, interviews, and documentation. Data analysis techniques are reduction, data presentation and conclusion. Technique of validity of research data is source triangulation. There are 2 obstacles faced by the role of women in reducing the risk of the earthquake and tsunami disaster in Air Tawar Barat Village, namely internal and external constraints. The results show that the internal constraints are that BPBD has not integrated gender issues into disaster risk reduction activities, while the external obstacle is the lack of understanding, awareness, vigilance and concern for the women community.